FAKTOR – FAKTOR YANG MEMPENGARUHI BRAND TRUST DAN BRAND COMMITMENT PADA SITUS BUKALAPAK.COM DI SURABAYA - ARDYANTO, AGUNG SEPTIAN (Universitas Katolik Widya Mandala Surabaya, 2013)
The purpose of this research is to know the influence of the Security, Privacy, Brand Name, Word of Mouth, Experience, Trust and Brand Information to influence Brand Trust of Brand Commitment on the online store on the site www.bukalapak.com. The design of this research is research that explains the causal relationship cause due to the influence of the free variables of variables are bound. The variable in this study i.e. latent exogenous (non variable), namely: Security, Privacy, Brand Name, Word of Mouth, Experience, Information. While mediating (between variables), namely: Brand Trust and endogenous latent (variable), namely: Brand Commitment. The number of samples as many as 170 research samples. Technique of data analysis using Structural Equation Modeling with Lisrel program. The findings of this study indicate that the influence of the Security, Privacy, Brand Name, Word of Mouth, Experience, Trust and Brand Information to influence Brand Trust of Brand Commitment on the online store on the site www.bukalapak.com. Brand Trust is able to strengthen the influence of the free variables of the Brand Commitment. That confidence may provide a reference brand for consumers that have a commitment to and confidence in the brand, the brand itself can strengthen the influence of the Security, Privacy, Brand Name, Word of Mouth, Experience, Information